THE EFFECTIVENESS OF EXPLORING LOCAL WISDOM FROM YOUTUBE: AN INVESTIGATION ON THE INDONESIAN HIGHER EDUCATION STUDENTS’ DANCE PERFORMANCE ACROSS GENDER - Fuji Astuti (LPMPP Universitas Negeri Yogyakarta, 2021)
Technology-based media can increase students’ motivation more than equipping their teaching materials with traditional ones. This article aims to describe the difference between the dance performance of students taught by exploring local wisdom from YouTube and those who are taught by the conventional method. This quasi-experimental study describes whether local wisdom and technology via YouTube can effectively increase Indonesian students’ dance performance at the higher education level. A number of 205 students participated in this research. A dance performance test, two scoring rubrics, and a questionnaire were used. The result of statistical analysis shows that exploring the values of local wisdom from YouTube videos can give a significant effect on students’ dance performance with sig. = .000. In terms of gender, there is a significant difference between female and male students after being taught by exploring local wisdom from YouTube videos (sig. = .000). Moreover, females also achieve better than males in terms of creativity including fluency, flexibility, elaboration, and originality of their dance products. The results of the questionnaire reveal that students appreciate and feel helped by integrating local wisdom and YouTube videos in the choreography course and agree that the values of local wisdom direct their dance performance in terms of movement, attitude, costume, and creativity.